2014
DOI: 10.3109/14764172.2014.946049
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of excimer laser on vitiligo treatment in comparison with a combination therapy of Excimer laser and tacrolimus in an Iranian population

Abstract: Our study shows that Iranian patients with vitiligo who received a combined treatment course with 308-nm EL and tacrolimus 0.1% experienced significantly higher levels of repigmentation in comparison with laser therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In that study after 24 sessions, >75% repigmentation was achieved in 50% of the lesions that received combined therapy, while it was only 20% for the lesions that received monotherapy (11). Studies conducted at later stages also supported this outcome (22)(23)(24). It was reported that this synergistic effect might be due to the activation of pathways responsible for melanocyte migration and melanogenesis (19).…”
Section: Discussionmentioning
confidence: 86%
“…In that study after 24 sessions, >75% repigmentation was achieved in 50% of the lesions that received combined therapy, while it was only 20% for the lesions that received monotherapy (11). Studies conducted at later stages also supported this outcome (22)(23)(24). It was reported that this synergistic effect might be due to the activation of pathways responsible for melanocyte migration and melanogenesis (19).…”
Section: Discussionmentioning
confidence: 86%
“…The safety and efficacy of topical calcineurin inhibitors in patients with vitiligo has been evaluated in recent years [50][51][52][53][54][55][56][57][58][59][60][61]. Two left-right comparative studies showed that tacrolimus had similar effects to clobetasol propionate 0.05% in the treatment of pediatric patients [51,52].…”
Section: Topical Calcineurin Inhibitorsmentioning
confidence: 99%
“…After the clinical trial, 61.7% of patients continued to use tacrolimus ointment, indicating that they were satisfied with the effects of tacrolimus and had a strong desire to continue the treatment [57]. Some studies showed that tacrolimus combined with narrowband UVB or 308-nm excimer laser therapy was superior to phototherapy alone or tacrolimus monotherapy [60,61]. The common side-effects of tacrolimus ointment were skin irritation (burning sensation, pruritus and erythema).…”
Section: Topical Calcineurin Inhibitorsmentioning
confidence: 99%
“…Phototherapy combined with other treatments can provide higher efficiency, quicker onset of action and better adherence to treatment 6 . Since Kawalek et al 14 first reported the synergistic effect of topical tacrolimus combined with 308‐nm EL in 2004, many studies have demonstrated that 308‐nm EL combined with TCI is more efficient than 308‐nm EL monotherapy in the treatment of vitiligo 15–20 . However, there is no literature illuminating combined therapy is better for the special vitiligo region like the periocular skin.…”
Section: Introductionmentioning
confidence: 99%